Real Options, Business Valuation, and Dynamic Decisions - Cong, Lin William (Journal of Management Policy and Practice, 2017)
This paper surveys recent theoretical developments on real options, and discusses its applications in business valuations and dynamic corporate decisions. In particular, the paper highlights the issues in the timing and design of sales of real options, as often observed in the auctions of natural resources, real estate sales, patents and licenses, and start-up companies. The choice of payment security and seller’s commitment all play integral roles in shaping equilibrium outcomes for option exercise, revenue, and social welfare